PENGARUH PENGGUNAAN MEDIA AUDIO VISUAL TERHADAP MINAT BELAJAR BIOLOGI SISWA PADA MATERI PLANTAE DI KELAS X SMA SWASTA AMAL BAKTI MEDAN TAHUN PEMBELAJARAN 2016/2017 - Radita Aulia Swastika; Ahmad Shafwan S Pulungan; Ratna Kekal Bariani (Universitas Negeri Medan, 2017)
This study aims to determine the effect of the use of audio visual media on the interest of learning biology of students on plantae material in the class X Private High School Amal Bakti Medan in the 2016/2017 academic year. The type of this research is descriptive research. The subject of this research is the students of grade X of Private High School Amal Bakti. Samples used 38 students of class X. The research instrument used is a test about questionnaire as many as 30 questions with closed answer. The use of audio visual media in the learning process affect the interest of learning student on the subject of biology on Plantae material. The results of this study indicate that overall students experience increased interest in learning of 4.12% after the learning process in aids with audio-visual media in the form of learning videos. And the indicators used to measure interest in learning, namely pleasure (13.1%), curiosity (4.7%), interest (5.7%), comfort (1%) and student enthusiasm (3, 9%) towards biology teachers and biology lessons.Keyword: audio visual media, interest learning, Plantae